Breakfast, lunch, and dinner sign: a hallmark of flea and bedbug bites - Peres, Gabriel [UNESP]; Tacito Yugar, Lara Buonalumi [UNESP]; Haddad Junior, Vidal [UNESP] (Soc Brasileira Dermatologia, 2018)
Human, dog, and cat fleas, as well as bedbugs, feed by biting their victims, causing acute prurigo, which is aggravated in sensitized victims (papular urticaria). The lesions appear in the classic breakfast, lunch, and dinner pattern. There are two main explanations: the parasites map the skin area in search of the best places to bite, and their removal when victim scratches, and then reattach to the skin. Treatments aim to control pruritus, as well as hypersensitivity reactions when necessary. Prevention is based on environmental control measures. The breakfast, lunch, and dinner sign is a definitive marker for diagnosis and the parasite's identification and control.
Keywords: Bedbugs; Flea infestations; Parasites; Prurigo